1997
DOI: 10.1002/art.1780400510
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of early Rheumatoid Arthritis with minocycline or placebo. Results of a Randomized, double‐blind, placebo‐controlled trial

Abstract: Objective. To determine if minocycline is an effective therapy for seropositive rheumatoid arthritis (RA) when used within the first year of disease.Methods. The Rheumatoid Arthritis Investigational Network enrolled 46 patients with RA of <1 year duration into a 6-month study of minocycline (100 mg twice daily) versus placebo. All patients were rheumatoid factor positive. The primary end point of the study was successful completion of 6 months of treatment with no drug toxicity while maintaining 50% improvemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
71
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(74 citation statements)
references
References 41 publications
2
71
1
Order By: Relevance
“…Recently, randomized doubleblind, placebo-controlled trials have demonstrated the efficacy of minocycline in improving the clinical parameters of RA (106)(107)(108)(109). Importantly, one trial showed long-term benefit of minocycline and a decrease in radiographic progression in a subset of patients who were positive for the HLA shared epitope (HLA-DR4ϩ) (110).…”
Section: Pharmacologic Treatment Of Ramentioning
confidence: 99%
“…Recently, randomized doubleblind, placebo-controlled trials have demonstrated the efficacy of minocycline in improving the clinical parameters of RA (106)(107)(108)(109). Importantly, one trial showed long-term benefit of minocycline and a decrease in radiographic progression in a subset of patients who were positive for the HLA shared epitope (HLA-DR4ϩ) (110).…”
Section: Pharmacologic Treatment Of Ramentioning
confidence: 99%
“…Minocycline has been found to be therapeutic in multiple diseases whose pathogenesis is significantly T cell driven by modulating cellular activation and function. In rheumatoid arthritis patients, minocycline significantly improved clinical symptoms and increased the frequency of remissions leading to its usage as a disease modifying anti-rheumatic drug (7)(8)(9). Studies using CD4 ϩ T cell clones derived from the synovium of an rheumatoid arthritis patient showed that minocycline decreased activation-induced proliferation and inflammatory cytokine production (10).…”
mentioning
confidence: 99%
“…Paulus criteria [6])-based definition of improvement, utilizing only a higher threshold of improvement (7,8). With potent new therapies on the horizon for RA, it may be reasonable to "raise the bar" and define RA improvement by more substantial changes in RA core set measures, such as requiring at least 50% or even 70% improvement.…”
mentioning
confidence: 99%